Differential Muscle Involvement in Mice and Humans Affected by McArdle Disease. Issue 5 (May 2016) - Krag, Thomas O.; Pinós, Tomàs; Nielsen, Tue L.; Brull, Astrid; Andreu, Antoni L.; Vissing, John
Abstract : McArdle disease (muscle glycogenosis type V) is caused by myophosphorylase deficiency, which leads to impaired glycogen breakdown. We investigated how myophosphorylase deficiency affects muscle physiology, morphology, and glucose metabolism in 20-week-old McArdle mice and compared the findings to those in McArdle disease patients. Muscle contractions in the McArdle mice were affected by structural degeneration due to glycogen accumulation, and glycolytic muscles fatigued prematurely, as occurs in the muscles of McArdle disease patients. Homozygous McArdle mice showed muscle fiber disarray, variations in fiber size, vacuoles, and some internal nuclei associated with cytosolic glycogen accumulation and ongoing regeneration; structural damage was seen only in a minority of human patients. Neither liver nor brain isoforms of glycogen phosphorylase were upregulated in muscles, thus providing no substitution for the missing muscle isoform. In the mice, the tibialis anterior (TA) muscles were invariably more damaged than the quadriceps muscles. This may relate to a 7-fold higher level of myophosphorylase in TA compared to quadriceps in wild-type mice and suggests higher glucose turnover in the TA. Thus, despite differences, the mouse model of McArdle disease shares fundamental physiological and clinical features with the human disease and could be used for studies of pathogenesis and development of therapies.